2017
DOI: 10.1002/jbm.a.36000
|View full text |Cite
|
Sign up to set email alerts
|

In vivo bone tunnel evaluation of nanoparticle‐grafts using an ACL reconstruction rabbit model

Abstract: Acellular human gracilis tendons conjugated with gold nanoparticles (AuNP) and hydroxyapatite nanoparticles (nano-HAp) were used as a graft in an anterior cruciate ligament (ACL) reconstruction rabbit model. The ACLs of 11 New Zealand rabbits were reconstructed using grafts conjugated without nanoparticles, with AuNP only, and with both AuNP and nano-HAp. Semi-quantitative histological scoring of bone tunnel portion of grafts was performed after 14 weeks. Bone tunnels were scored for graft degeneration, graft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The number of ACLR surgery is enormous. According to the statistics of the United States, there are more than 200,000 patients with ACL injury each year and at least 100,000 patients are received ACLR surgery [ 3 , 4 ]. In ACLR, the choice of grafts is very important.…”
Section: Introductionmentioning
confidence: 99%
“…The number of ACLR surgery is enormous. According to the statistics of the United States, there are more than 200,000 patients with ACL injury each year and at least 100,000 patients are received ACLR surgery [ 3 , 4 ]. In ACLR, the choice of grafts is very important.…”
Section: Introductionmentioning
confidence: 99%
“…After 14 weeks, all the grafts were intact with new, organized host fibrous connective tissue present in all graft types. 34 As a result of the small sample size, there were no statistically significant differences between the control and experimental grafts. However, several promising trends were observed.…”
Section: Discussionmentioning
confidence: 93%
“…After 14 weeks, all the grafts were intact with new, organized host fibrous connective tissue present in all graft types. 34…”
Section: Discussionmentioning
confidence: 99%
“…This was examined in a rabbit model after treating the tendon with AuNPs (20 nm) alone or AuNPs with hydroxyapatite nanoparticles (nan-HAP; <40 nm). 46 This approach improved the functional regeneration of tendons and ligaments, thereby enhancing the regenerative process of the ACL. The study revealed that treating tendons with AuNPs (20 nm) enhanced the healing and remodeling of the decellularized grafted tendons by forming a new intact vascularized fibrous construct in the host.…”
Section: Improving Decellularized Matrices Via Npsmentioning
confidence: 99%